Approaches to discourse particles - Fischer, Kerstin, 1966- (Studies in pragmatics, 2006)
Presents the spectrum of approaches to discourse particles / markers, whilst ensuring that the differences and similarities between the approaches are clear and comparable. This book features researchers from different linguistic backgrounds, describing their particular ways of accounting for some of the most important problem areas.